VARIASI PERTUMBUHAN DAN PARAMETER GENETIK UJI KETURUNAN JATI UMUR 5 TAHUN DI GUNUNG KIDUL, YOGYAKARTA - Hamdan Adma Adinugraha; Sugeng Pudjiono; Mahfudz Mahfudz (Jurnal Pemuliaan Tanaman Hutan, 2013)
This study was conducted to observe growth variation and genetic parameters of progeny test of teak (Tectona grandis Linn. F) in Gunung Kidul at 5 years of age. The progeny test of teak was laid-out in a randomized complete block design consisting of 120 families, 6 blocks, 3 tree-plots. Measurement was conducted annually for traits tree height, dbh, stem straightness, branching type and individual tree volume. The results of study showed that the mean of survival rate reached 84.72%, which was varied from 55.56 to 100%. Among tested families and populations, all measurement traits showed significant differences. The average of growth traits werw 5.86 m for tree height, 5.69 cm for dbh and 0.015 m3 for individual stem volume. In case of form traits, the average were 2.12 for stem straightness and 1.90 for branching type. Estimated family heritability were 0.166 for tree height, for dbh, 0.245 for stem straightness, 0.140 for the branching type and  0.289 for individual  stem volume.